Understanding the Relationship between Atherogenic Index of Plasma and Cardiovascular Disease Risk Factors among Staff of an University in Malaysia - Myat Su Bo; Whye Lian Cheah; Soe Lwin; Tin Moe Nwe; Than Than Win; Myint Aung (Journal of Nutrition and Metabolism)
Background. Atherogenic index of plasma (AIP) was found to be one of the strongest markers in predicting the cardiovascular disease (CVD) risk. This study was to determine the AIP and its relationship with other CVD risk factors. Materials and Methods. This cross-sectional study was done among 349 staff of a public university in Sarawak. Data were collected using questionnaire, blood sampling, and anthropometric and blood pressure measurement. Data were analyzed using IBM SPSS version 20. Results. A total of 349 respondents participated with majority females (66.8%), aged 38.5 ± 7.82 years. Nearly 80% of the respondents were overweight and obese, 87.1% with high and very high body fat, and 46.9% with abnormal visceral fat. For AIP category, 8.9% were found to be in intermediate and 16.4% were at high risk. Elevated lipid profile showed that total cholesterol (TC) is 15.5%, low density lipoprotein (LDL) is 16.1%, and triglyceride (TG) is 10.6%. AIP was significantly correlated with body mass index (r=0.25), visceral fat (r=0.37), TC (r=0.22), LDL (0.24), HDL (r=−0.72), TG (r=0.84), glucose (r=0.32), systolic blood pressure (r=0.22), and diastolic blood pressure (r=0.28). Conclusion. It indicated that AIP is associated with other CVD risk factors. Modification of lifestyle is strongly recommended.